2021
DOI: 10.3389/fpsyg.2021.526942
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Distance Expressed by Driving Support Agent’s Utterance on Psychological Acceptability

Abstract: In this study, we discuss the psychological acceptability of an utterance strategy used by the Driving Support Agent (DSA). Previous literature regarding DSA suggests that the adoption of a small robot as a form will increase acceptability. However, the agent’s utterance has been reported as a problem faced by the user. Therefore, in this study, we designed the agent’s utterance using politeness strategy as described by Brown and Levinson’s famous sociolinguistics and pragmatics theory and analyzed its accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
10
2
Order By: Relevance
“…Miyamoto et al [5,6] and Lee et al [7] partially verified the effects of politeness strategies in DSA. In the study by Miyamoto et al [5,6], the effects of PPS and NPS were compared, and PPS was evaluated significantly higher than NPS. In contrast, it was shown that there are some users who prefer NPS to PPS [5].…”
Section: Politeness Research On Agentsmentioning
confidence: 93%
See 4 more Smart Citations
“…Miyamoto et al [5,6] and Lee et al [7] partially verified the effects of politeness strategies in DSA. In the study by Miyamoto et al [5,6], the effects of PPS and NPS were compared, and PPS was evaluated significantly higher than NPS. In contrast, it was shown that there are some users who prefer NPS to PPS [5].…”
Section: Politeness Research On Agentsmentioning
confidence: 93%
“…In the study by Miyamoto et al [5,6], the effects of PPS and NPS were compared, and PPS was evaluated significantly higher than NPS. In contrast, it was shown that there are some users who prefer NPS to PPS [5]. The study of Lee et al [7] showed the effectiveness of DSA that used NPS.…”
Section: Politeness Research On Agentsmentioning
confidence: 99%
See 3 more Smart Citations